(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
This article analyzes the role and significance of the mass media in the formation of political consciousness and political culture. The impact of the mass media on socio-political processes, the role of citizens in increasing their political thinking and activity in the political decision-making process is covered from a scientific point of view. It also considers how the reforms being implemented in the information sector in Uzbekistan, freedom of speech and the press affect the development of political culture.